Culture-Based History Teaching Materials as a Process of Cultivating Nationalism in Elementary Schools in Indonesia and Malaysia - Aan Suryana; Sri Pajriah; Umi Saidatul Arryennah Bt. Madsah; Wulan Sondarika; Pani Silviani (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
History education in Indonesian and Malaysian elementary schools in the 21st century faces many challenges: limited time, inadequate facilities and infrastructure, textbook-based history teaching materials, frequent curriculum changes, and obstacles to instilling nationalism in students. This study aims to analyse culture-based history teaching materials in Indonesian and Malaysian elementary schools as a process of instilling nationalism in students. The study used a qualitative literature study approach by identifying and selecting relevant literature sources. The data collection method used literature documentation. The data analysis technique used was descriptive qualitative. The results show that culture-based history teaching materials in Indonesia emphasise the integration of local cultural values, such as noble values, religion, morals, and truth, into the learning process. Meanwhile, in Malaysia, history is a compulsory subject taught at the elementary, secondary, and tertiary levels within the Malaysian curriculum. History education is implemented with a Malaysia-centred approach with the aim of instilling a sense of love for the homeland, patriotism, and the formation of a united Malaysian nation. History teaching materials integrate cultural heritage education into the Malaysian education curriculum. The implications of this research are that this research shows that cultural-based history teaching materials are effective in instilling nationalism and noble values in students.